Careful Cheating: People Cheat Groups Rather than Individuals - Amir, Amitai; Kogut, Tehila; Bereby-Meyer, Yoella (Frontiers in Psychology, 2016)
Cheating for material gain is a destructive phenomenon in any society. We examine the extent to which people care about the victims of their unethical behavior—be they a group of people or an individual—and whether they are sensitive to the degree of harm or cost that they cause to these victims. The results of three studies suggest that when a group (rather than a single individual) is the victim of one’s behavior, the incidence of cheating increases only if the harm to the group is presented in global terms—such that the cheating might be justified by the relatively minor harm caused to each individual in the group (Study #1 and #3). However, when the harm or cost to each individual in the group is made explicit, the tendency to cheat the group is no longer apparent and the tendency to cheat increases when the harm caused is minor—regardless of whether the victim is an individual or a group of people (Study #2). Individual differences in rational and intuitive thinking appear to play different roles in the decision to cheat different type of opponents: individual opponents seem to trigger the subject’s intuitive thinking which restrains the urge to cheat, whereas groups of opponents seem to trigger the subject’s rational mode of thinking which encourage cheating.